P141 Infliximab therapy for inflammatory pouch pathology: a multi-centre retrospective study. (16th January 2018) - Segal, J; Penez, L; Mclaughlin, S; Mullish, B; Quraishi, M; Ding, N; Kandiah, K; Samaan, M; Irving, P; Faiz, O; Clark, S; Hart, A
Abstract: Background: Restorative proctocolectomy (RPC) with ileal pouch-anal anastomosis is considered the procedure of choice in patients with ulcerative colitis (UC) refractory to medical therapy. Subsequent inflammation of the pouch is a common complication and in some cases fails to respond to antibiotics, the mainstay of treatment. In such cases, corticosteroid, immunomodulatory or biologic treatments are often considered. However, our understanding of the efficacy of anti-tumour necrosis factor (anti-TNF) medications for both Crohn's like complications and chronic refractory pouchitis are based on studies that include relatively small numbers of patients. Methods: Aims: To assess the effectiveness and safety of infliximab for pouch-related inflammatory problems. The two primary outcomes of interest were the development of pouch failure, which we defined as the need for an ileostomy, and non-response to infliximab therapy, which we defined as primary non-response to infliximab or anti-infliximab antibody formation. This was an observational retrospective multi-centre study. A template data collection sheet was completed by each sub-investigator at each participating centre to collect the variables of interest. Potential patients were identified by using each hospital's infliximab and pouch database. We included patients who received infliximab infusions to allow us to retrieve the follow-up data. Results: Thirty-four patients met the inclusion criteria. Twenty-six (76%) received infliximab for chronic refractory pouchitis and eight (24%) for Crohn's-like complications of the pouch. Twenty-one (62%) of patients who were initiated on infliximab for inflammatory pouch-related problems had non-response to infliximab. Following infliximab treatment failure, 10/21 (47%) patients required a stoma, the median time from initiation on infliximab to failure was 250 days range (42–1544). 15/21(71%) of those who failed infliximab did so within the first year. Conclusions: The use of infliximab is associated with a high incidence of primary non- response or pouch failure. Once escalation to infliximab medication for pouch-related problems is considered, patients should be carefully counselled about a high incidence of failure and therefore alternatives, including surgery should be discussed.